Envelhecimento e vida vocacional : a repercussão da itinerância no processo de viver e envelhecer das idosas religiosas - Martinelli, Marisa (2014)
In the course of life, consecrated religious, who are active in the apostolate, live on a mobile basis. Itinerant is a person who travels to several different places, in order to exercise certain function such as: itinerant preacher. In order to describe the meanings and implications of itinerancy in the living and aging process of elderly consecrated religious, a research was made, using an exploratory and descriptive qualitative approach. This was developed with 28 elderly women of a religious congregation in the north of the State of Rio Grande do Sul. Data collection was conducted through individual interviews, recorded in the period of April-July 2013. Thematic analysis was used to build the categories: vocational choice: a designated mission, family guidance in vocational choice, constructive/healthy decision and inevitable suffering, itinerant disengagement in consecrated religious life. The results show that not all religious women prepare themselves for old age.The itinerant disengagement process is felt and perceived ambiguously by the elderly and become more difficult in the aging period. Spirituality is what directs and strengthens their lives; it is the reason of the option for VRC (Consecrated Religious Life). The family support is of paramount importance. There is also the desire for investment in aging of consecrated religious, so that their gifts and talents be recognized and developed and that their autonomy is maintained